New horizon for veterinarians in aquaculture - Mohamed Din, Mohamed Shariff (Universiti Putra Malaysia Press, 2004)
For the last 20 years aquaculture has been the fastest growing food producing sector in the world. The rapid growth of aquaculture, with transfer of live aquatic animals between countries and between continents has resulted in severe financial losses due to transmission and outbreak of diseases. The authorities concerned with fisheries have realized that disease is a major constraint for the development of sustainable aquaculture. Lack of comprehensive quarantine system, insufficient knowledge on fish health and uncontrolled use of antibiotics are some of the issues associated with the widespread of aquatic diseases. This paper highlights that capacity building in aquatic animal health is a significant issue that has not been addressed appropriately. Veterinarians are a natural choice and are being sought to play an important role in aquatic animal health management. However, the present veterinary curriculum does not cater this need. The scope for veterinarian in aquatic health management and aquatic medicine is enormous. Veterinary institutions should be aware of this new rapidly emerging field and make necessary changes so as veterinarians can play a key role for the development of sustainable aquaculture industry.